Operating Room Nurses’ Lived Experience of the Challenges Arising after Admitting Emergency Patients: A Phenomenological Study - Alireza jafarkhani; Behzad Imani; sina Ghasemi (پیاورد سلامت)
Background and Aim: Today, an important part of the surgeries performed in the operating room are emergency surgeries. Surgeries are generally necessary in the face of acute life-threatening conditions. Today, due to the increase in the number of emergency surgeries performed in hospitals and the challenging nature of these surgeries, several problems have arisen in the operating room. This study aimed to explain the lived experience of operating room nurses of the challenges that arise following the admission of emergency patients. Materials and Methods: This research is a qualitative study that was conducted using descriptive phenomenology in 2023 in all hospitals affiliated with Hamadan University of Medical Sciences. The samples of this study were selected using purposeful and snowball sampling. In this research, data were collected through 10 semi-structured interviews with operating room nurses. The data obtained were analyzed to determine the main and sub-categories using Colaizzi’s method Results: The results of this study showed that the average age of the participants was 46.2 years and their average work experience was 18.5 years. After analyzing the interviews, it was found that the challenges arising from the admission of emergency patients from the perspective of the experiences of operating room nurses are classified into three main themes and 10 subthemes. The main themes of this study include operating room supplies and infrastructure (structural limitations of the operating room, provision of human resources for emergency surgeries, provision of equipment and tools required for surgery, and negligence in providing timely medical services), clinical risks during surgery (threat to patient safety, disregard for observing the principles of sterility and the patient's unique physical condition), and coordination and communication (unconstructive interaction of the surgeon with staff, unusual behaviors of companions in the operating room, and insufficient support for the patient by others). Conclusion: To prevent challenges, early identification is essential. By planning and implementing preventive measures, improving nurse training, improving infrastructure, and strengthening interdisciplinary collaboration, we can improve the quality of emergency surgical procedures and increase patient satisfaction.